“Central” and “peripheral” adaptation pathways of entangled agrifood systems transformations - Dagli, Winifredo (Frontiers in Sustainable Food Systems, 2022)
In the agrifood systems of developing countries, local adaptation actions and pathways often interact with other climate and development responses, creating new trade-offs, uncertainties, and potentially maladaptive outcomes. While knowledge on the interacting pathways of adaptation is expanding, previous studies have focused on complex systems dynamics, and studies that address the human, social, and political forces that drive the cascading of risks between different coupled social-ecological systems are few. This paper aims to examine climate adaptation trade-offs, uncertainties, and maladaptation through an interdisciplinary analysis of two interacting pathways of transformational adaptation in the Philippines: the post 2004 disaster rural transformations in the coconut-producing municipality of Infanta and a state-led urban water resilience strategy for the capital region of Metro Manila. Data were collected from January 2021 to March 2022 through ethnographic field visits, participant observation, focus group discussions, semi-structured interviews, geospatial analysis, multicriteria mapping sessions, and review of planning documents and secondary data sources. Key findings suggest that the pathways of transformation and their entanglement are rooted in historical processes of change and that maladaptation is contingent on the political relations between the “central” and “peripheral” pathways. Overall, the paper offers a significant contribution to adaptation research in the agrifood systems of developing countries as it calls for a deeper kind of collective reflexivity and action that can transform narrow notions and practices of resilience and sustainable development.